Characterization of Streptococcus mitis subsp. carlssonii isolated from human vagina: prevalence, phenotypic, and genomic insights - Montecillo, Jake Adolf V.; Lee, Jung Hwa; Yoo, Heon Jong; Lee, Yoo-Young; Park, Chul Min; Cho, Angela; Lee, Hyunsu; Kim, Jong Mi; Lee, Nan Young; Park, Sun-Hyun; Park, Nora Jee-Young; Han, Hyung Soo; et al. (Frontiers in Microbiology, 2025)
The genus Streptococcus is a heterogenous group of commensal and pathogenic bacteria. Members of this genus are classified into two major groups, the pyogenic group and the viridans group streptococci (VGS). VGS are frequently found as normal members of the human microbiome and are regarded as commensals. In this work, we characterized a VGS strain isolated from the vaginal swab sample of a Korean patient diagnosed with endometrial cancer. Phylogenetic, phenotypic, and genome-based analyses confirmed the classification of the strain K0074 as a member of the S. mitis complex. Based on the phylogenetic analyses, the species belonged to the recently established Streptococcus mitis subsp. carlssonii. The strain was found to be rare in the vaginal microbiome, but prevalent in the oral and nasal microbiome samples. K0074 neither triggered an inflammatory response nor caused cytolytic and cytotoxic effects on human cervical cancer cell line. Genome analysis uncovered the genetic basis of the strain's metabolism, virulence factors, and potential antimicrobial resistance phenotypes. Moreover, comparative genomics of the strain and closely related species and subspecies highlighted their striking differences in gene properties and biological functions. Overall, the new strain exhibited low virulence and pathogenic potentials and thus, is regarded as a commensal member of the human microflora. The genetic divergence of K0074 from closely related strains offers a compelling foundation for future investigations into the strain's potential functional specialization and its adaptation within the vaginal microbiome.